PERSEPSI MAHASISWA AKUNTANSI MENGENAI PENGGELAPAN PAJAK - Fitri; Ulfa Rabiyah; Anita Nursanti (JURNAL LENTERA BISNIS, 2025)
This study aims to test the differences in accounting students' perceptions regarding tax evasion. Respondents in this study were undergraduate accounting students in Makassar with a sample size of 90 respondents. This study used quantitative data analysis methods. The data collection method uses primary data by conducting a data survey technique and then processed using SPSS. The findings of this study show that there is no difference in perception between male and female students regarding tax evasion.